Supreme Courts’ jurisprudence as a dispute avoidance mechanism? - Capasso, Valentina (Civil Procedure Review, 2018)
Starting from a comparative and economic perspective, this article aims to assess the efficiency of recent reforms of civil procedure, especially focusing on Italian and French experiences. On the one hand, it underlines that convergences in European Countries regulatory actions in the field should not be overestimated: even equal reforms may end up with different outcomes, because of differences in the starting backgrounds (whether economical or cultural). On the other hand, it casts doubts about the effectiveness of regulations imposing ADR mechanisms as a pre-condition to legal proceedings or providing for appeals selection: as Positive Law and Economics shows, mandatory mediation or conciliation is unlikely to overcome parties cognitive bias, while side effects brought by skimming mechanisms may undermine their benefits. Rather, starting from the assumption that parties estimates of the process outcome strongly affect their choice between settlement and litigation, it is suggested that Supreme Courts jurisprudence plays a fundamental role in determining incoming flows, and that its inconsistency increases demand inflation.